2014
DOI: 10.1002/pi.4674
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyurethane/triethanolamine functionalized multi‐walled carbon nanotube nanocomposites as remote induced smart materials

Abstract: Triethanolamine functionalized multi-walled carbon nanotubes (TEA-f-MWCNTs)/hyperbranched polyurethane nanocomposites were prepared by the in situ polymerization technique. The functionalization of the MWCNTs was confirmed by Fourier transform infrared spectroscopy and Raman spectroscopy studies. The homogeneous distribution and the strong interfacial interaction of TEA-f-MWCNTs with the polyurethane chains were confirmed by transmission electron microscopy and Fourier transform infrared spectroscopy studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…A TGA thermogram is obtained by recording the change in weight of the polymer either against temperature or time. In most of the cases, the thermograms clearly indicate higher thermal stability of the pristine bio-based hyperbranched polyurethane matrix after incorporation of different nanomaterials (43)(44)(45)(46)(57)(58)(59)(60)(61)(62). The study also confirmed that nanomaterials are thermal insulators and mass transport barriers to the volatile products produced during decomposition.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…A TGA thermogram is obtained by recording the change in weight of the polymer either against temperature or time. In most of the cases, the thermograms clearly indicate higher thermal stability of the pristine bio-based hyperbranched polyurethane matrix after incorporation of different nanomaterials (43)(44)(45)(46)(57)(58)(59)(60)(61)(62). The study also confirmed that nanomaterials are thermal insulators and mass transport barriers to the volatile products produced during decomposition.…”
supporting
confidence: 76%
“…of such nanocomposites are essential for their various applications. Most of the studies showed significant improvement in such mechanical properties of bio-based hyperbranched polyurethanes even at very low loading of suitable nanomaterials (43)(44)(45)(46)(57)(58)(59)(60)(61)(62). The extent of improvement depends on the actual interfacial interactions between nanomaterial and bio-based hyperbranched polyurethane (Fig.…”
mentioning
confidence: 94%
See 3 more Smart Citations